Traumatic Brain Injury - Neurobiology, Diagnosis and Treatment 2019
DOI: 10.5772/intechopen.85432
|View full text |Cite
|
Sign up to set email alerts
|

Post Concussion Syndrome

Abstract: Post-concussion syndrome (PCS) is a complex disorder and the complete pathophysiology is still not completely understood. PCS can be subcategorized into physiological PCS, vestibulo-ocular PCS, cervicogenic PCS, and mood-related PCS based on predominant clinical signs and symptoms. Physiological PCS is the most classic type of PCS and is due to global metabolic dysfunction in the brain which affects the autonomic nervous system (ANS) and cerebral blood flow (CBF) autoregulation. This is suspected to be the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 132 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…Similar IL-8 median values in both mild head injury subgroups may result from the fact that the trauma per se significantly affects the course of inflammatory response. On the other hand, neuropathological changes manifested in the form of concussion after head injury may result from functional disturbance rather than more severe structural brain damage [ 29 , 30 , 31 ], which could also account for the lack of difference in IL-8 levels. This postulate was confirmed by Schimmel et al [ 32 ], who indicated that neuroinflammation in response to traumatic brain injury increases neural cell death by interfering with endogenous repair mechanisms and acts through chemokines, cytokines and other inflammatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Similar IL-8 median values in both mild head injury subgroups may result from the fact that the trauma per se significantly affects the course of inflammatory response. On the other hand, neuropathological changes manifested in the form of concussion after head injury may result from functional disturbance rather than more severe structural brain damage [ 29 , 30 , 31 ], which could also account for the lack of difference in IL-8 levels. This postulate was confirmed by Schimmel et al [ 32 ], who indicated that neuroinflammation in response to traumatic brain injury increases neural cell death by interfering with endogenous repair mechanisms and acts through chemokines, cytokines and other inflammatory molecules.…”
Section: Discussionmentioning
confidence: 99%